TAKING INTO ACCOUNT THAT ONE OF THE FACTORS IN PREPARING YOUNG WOMEN FOR FAMILY LIFE IS MARRIAGE, WHICH HAS AN IMPACT ON THE STRENGTH AND STABILITY OF A FAMILY’S LIFE - Vakhabova Nasibakhon Abdulhamidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article discusses the importance of preparing young women for family life through marriage and the factors contributing to the strength and stability of a family. It highlights various aspects such as physical, sexual, legal, economic, moral-ethical, psychological readiness of youth for family life and emphasizes the significance of their contribution to the well-being of the family.